JUMPA Vol.3 No.2 Juni 2016 ANALISIS STRATEGI BISNIS PT. WILTAR USAHA GRUP: ANALISIS STRATEGI BISNIS PT. WILTAR USAHA GRUP - Enggal Sriwardiningsih Binus University (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
The floating docks are starting to need for the people who live in coastal areas. Factors of the tides is very difficult when they want to go to sea. The floating dock manufacturers PT.Wiltar Usaha Grup is providing a floating dock, but PT. Wiltar Usaha Grup is not the only manufacturer of a floating dock in Indonesia, this company should have competition between other companies. To achieve competitive advantage needed the right business strategy. Based on analisis SWOT at PT. Wiltar Usaha Grup. Finding result finds market penetration strategies as the best alternative business strategy. This strategy is derived from the analysis of internal and external factors using SWOT matrix analysis, analysis of internal-external matrix, grand strategy matrix analysis and SPACE matrix analysis.